(untitled) (International journal of artificial intelligence, 2024)
The fundamental building blocks of language acquisition, known as constructions, span from basic morphemes to complete sentences. While construction grammar offers advantages over traditional and generative approaches, its application to second language acquisition studies remains fragmented and unsystematic. This paper explores the developments in construction grammar theory and identifies key strategies for its effective integration into language teaching and learning. Furthermore, it addresses the methodological and practical limitations of existing research in this field.